ответ: -12.
Пошаговое объяснение:
можно по-другому...
можно применить формулу "разность кубов" для первых двух слагаемых:
(2a+1)³-(2a-1)³ = ((2a+1)-(2a-1))*((2a+1)²+(2a+1)(2a-1)+(2a-1)²) = 2*(2a+1)²+2*(2a+1)(2a-1)+2*(2a-1)²
и потом "увидеть" формулу "квадрат разности":
2*(2a+1)²+2*(2a+1)(2a-1)+2*(2a-1)² - 6*(2a+1)(2a-1) - 8(2a+1) =
= 2*(2a+1)²-4*(2a+1)(2a-1)+2*(2a-1)² - 8(2a+1) =
= 2 * ((2a+1)²-2*(2a+1)(2a-1)+(2a-1)²) - 8(2a+1) = 2*((2a+1)-(2a-1))² - 8(2a+1) =
= 2*2² - 8(2a+1) = 8 - 16a - 8 = -16a
-16*0.75 = -16*3/4 = -4*3 = -12
20 - а = б, а а= 20 - б
следовательно: (20-а) - с = 10 значит с = (20-а) - 10
а + с = (20-б) + ((20-а)-10))